2009
DOI: 10.1038/ismej.2009.12
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative population dynamics of microbial communities in plankton-fed microbial fuel cells

Abstract: This study examines changes in diversity and abundance of bacteria recovered from the anodes of microbial fuel cells (MFCs) in relation to anode potential, power production and geochemistry. MFCs were batch-fed with plankton, and two systems were maintained at different potentials whereas one was at open circuit for 56.8 days. Bacterial phylogenetic diversity during peak power was assessed from 16S rDNA clone libraries. Throughout the experiment, microbial community structure was examined using terminal restri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 28 publications
2
33
0
Order By: Relevance
“…These studies revealed that different EETactive communities were established with various carbon substrates and different electrode potentials, and both parameters clearly affected the final community composition (Torres et al, 2009;White et al, 2009;Freguia et al, 2010;Kiely et al, 2011). However, it is poorly understood how the substrates and electrode potentials affect the developmental processes of EET-active microbial communities, and how metabolic networks are established and maintained within the community.…”
Section: Introductionmentioning
confidence: 99%
“…These studies revealed that different EETactive communities were established with various carbon substrates and different electrode potentials, and both parameters clearly affected the final community composition (Torres et al, 2009;White et al, 2009;Freguia et al, 2010;Kiely et al, 2011). However, it is poorly understood how the substrates and electrode potentials affect the developmental processes of EET-active microbial communities, and how metabolic networks are established and maintained within the community.…”
Section: Introductionmentioning
confidence: 99%
“…In organic-rich sediments this may be members of the Geobacteraceae family 38,137 or other organisms. 138 Sulfide can be an important electron donor in sulfide-rich sediments. The abiotic oxidation of sulfide to elemental sulfur can provide some electrons, and then microorganisms such as Desulfobulbus, 139 can oxidize the elemental sulfur to sulfate, increasing the current contribution from sulfide.…”
mentioning
confidence: 99%
“…This outcome is similar the study by White et al who reported that communities were most different during startup and the similar community structures were observed once steadystate power had been achieved. 41 That study indicated that a diverse community structure had populated the anodes by peak power. This diversity was reduced under steady-state power production, indicating that the entire community observed in during SMFC startup does not contribute to electricity production.…”
Section: Discussionmentioning
confidence: 99%